Predict organizational citizenship behavior of the staff based on the factors of the psychological capital and staff of Ministry of Sport and Youth - Khaidan Hatmı; Mohhammad Reza Esmaeılı; Sayed Hamid Sajadı (Türk Spor ve Egzersiz Dergisi)
The aim of the present study was to predict organizational citizenship behavior of the staff of the Ministry of Sport and Youth in the west part of the country based on the factors of the psychological capital. The research methodology employed in the present study was applied and practical. The population consisted of all employees in the departments of the ministry of Sport and Youth in the west part of the country in the year 1394 including 266 personnel among whom 165 ones were selected as samples. In order to collect information, for collecting data on the psychological capital variable, the psychological capital questionnaire was used, and to collect data on the organizational citizenship behavior variable, the organizational citizenship behavior questionnaire was used. For data analysis, Kolmogorov-Smirnov inferential statistics were used to determine the normal distribution of data and the analysis of variance. The results of the study showed that there was a significant relationship between psychological capital and its components and organizational citizenship behavior. And the examination of the predictor variables showed that optimism, self-efficacy, and resilience (P≤0.05) can significantly explain the citizenship behavior variance.